2011
DOI: 10.1128/jcm.02356-10
|View full text |Cite
|
Sign up to set email alerts
|

Genotype of Varicella-Zoster Virus Isolates in South Korea

Abstract: Forty-four patients with herpes zoster and nine patients with varicella were enrolled. The median age of patients with herpes zoster was 59.5 (range, 10 to 77) years, and the median age of patients with varicella was 8 (range, 6 to 9) years. In sequence analysis of ORF 22, all isolates were genotype J, irrespective of the age group. In restriction enzyme analysis, 51 of 54 (94.3%) isolates contained a PstI site in ORF 38, and all isolates contained a BglI site in ORF 54. Our data suggest that genotype J has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Our results showed that the VZV strains isolated from patients in suburban Shanghai were primarily genotype J/clade 2 strains, suggesting that the distribution of VZV in China has significant geographical features. The results of our study, combined with those from studies in Japan (Inoue et al, 2010), Korea (Kim et al, 2011) and Mongolia (Enskhsaȋkhan et al, 2010), indicate that the majority of WT VZV strains in north-east Asia are genotype J/clade 2 strains. However, a small fraction of type M2 isolates were identified according to the 447 bp method in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Our results showed that the VZV strains isolated from patients in suburban Shanghai were primarily genotype J/clade 2 strains, suggesting that the distribution of VZV in China has significant geographical features. The results of our study, combined with those from studies in Japan (Inoue et al, 2010), Korea (Kim et al, 2011) and Mongolia (Enskhsaȋkhan et al, 2010), indicate that the majority of WT VZV strains in north-east Asia are genotype J/clade 2 strains. However, a small fraction of type M2 isolates were identified according to the 447 bp method in our study.…”
Section: Discussionsupporting
confidence: 79%
“…However, available data based on partial nucleotide sequences or restriction fragment length polymorphism suggest that all Korean isolates and Chinese isolates form a clade with Japanese isolates [16,17]. Thus, it is possible that the clade 2 could be extended to include China, which is geographically close to Japan and Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype M (including M1, M2, M3 and M4) is mainly detected in tropical regions in Africa and Central America [27,28]. Genotype J is the most prevalent VZV in the east Asia [29]. In the present study, one genotype J VZV strain was isolated from 26 samples with anti-VZV IgM positive.…”
Section: Discussionmentioning
confidence: 53%